A dança como instrumento de qualidade de vida - SOEIRO, Lauriane Ferreira (2019)
This research with the title "Dance as an Instrument of Quality of Life in gymnasiums" is related to my work in the academy environment as a dance instructor, and to understand in this meander the importance of dance for men and women a life better through changing habits. This study started with the question: What relationships are established between dance and quality of life in gymnasiums? My goal in this study was to demonstrate what the scientific production in the area has highlighted about dance and its relationships with the quality of life for the people who practice them. It is a bibliographical research of a qualitative character, in which the data were collected from the search of keywords such as "dance", "dance and quality of life" and "dance in gymnasiums", on the Organization's digital platforms World Health Organization (WHO), Scientific Electronic Library Online (Scielo) and Google Scholar. Thus, I selected between articles, monographs, dissertations and theses, only 06 studies, under the theme of quality of life and the performance of academies, in addition to the history of dance. As a result we have a low number of works on the subject and that dance is inseparable from improving the quality of life of those who practice it; that gymnasiums have a fundamental role in providing services to clients, promoting their satisfaction and permanence in these spaces and as an instrument of social well-being, dance is for everyone and not directed to a specific group.